Peanut Agribusiness Development Strategy (Arachis hypogaea) in Pracimantoro Sub-District - Pardede, Fitri; Harisudin, Mohamad; Barokah, Umi (Devotion : Journal of Research and Community Service, 2024)
Pracimantoro District is the largest peanut producing area in Wonogiri Regency with an average planting area of 381 Ha, productivity of 13.79 Kw/Ha, and production of 525.90 Tons. Farmers are expected to develop peanut agribusiness in the area. This study aims to formulate alternative strategies and determine the priorities of peanut agribusiness development strategies in Pracimantoro District. The basic method used is the descriptive method. Key informants are determined using convenience sampling techniques. Data collection techniques are carried out using observation, interview, recording, and triangulation of sources. The data analysis methods used include EFE and IFE Matrix, Grand Strategy Matrix, SWOT Matrix, and QSPM. The results showed that the peanut agribusiness development strategy was in quadrant I of Strength-Opportunity (S-O). The priority strategy that can be applied to the development of peanut agribusiness in Pracimantoro District is to develop production through improving the quality of peanuts.